Teaching About Disability: Involving Patients with Disabilities as Medical Educators - Minihan, Paula M.; Bradshaw, Ylisabyth S.; Long, Linda M.; Altman, Wayne; Perduta-Fulginiti, Sonya; Ector, Jeanette; Foran, Karen L.; Johnson, Lillian; Kahn, Paul; Sneirson, Robert (Disability Studies Quarterly, 2004)
No abstract available.